2008
DOI: 10.1186/1471-2407-8-381
|View full text |Cite
|
Sign up to set email alerts
|

Class I histone deacetylases 1, 2 and 3 are highly expressed in renal cell cancer

Abstract: BackgroundEnhanced activity of histone deacetylases (HDAC) is associated with more aggressive tumour behaviour and tumour progression in various solid tumours. The over-expression of these proteins and their known functions in malignant neoplasms has led to the development of HDAC inhibitors (HDI) as new anti-neoplastic drugs. However, little is known about HDAC expression in renal cell cancer.MethodsWe investigated the expression of HDAC 1, 2 and 3 in 106 renal cell carcinomas and corresponding normal renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 28 publications
7
121
0
1
Order By: Relevance
“…Recent clinical trials have indicated that HDAC inhibitors enhance the antitumor activities of several conventional chemotherapeutic and molecular-target drugs (25)(26)(27). Additionally, a previous study showed that HDACs were highly expressed in RCC, suggesting that HDAC inhibitors may be effective on RCC (28). Recently, the mTOR inhibitors everolimus and temsirolimus have been clinically used as a treatment against RCC, but are not curative.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have indicated that HDAC inhibitors enhance the antitumor activities of several conventional chemotherapeutic and molecular-target drugs (25)(26)(27). Additionally, a previous study showed that HDACs were highly expressed in RCC, suggesting that HDAC inhibitors may be effective on RCC (28). Recently, the mTOR inhibitors everolimus and temsirolimus have been clinically used as a treatment against RCC, but are not curative.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of HDAC2 is an independent prognostic factor for various types of tumors, including oral, ovarian, endometrial and gastric cancers (6,10,15). Fritzsche et al (25) reported a 60% increase in HDAC2 expression in renal cancer. Adams et al found that HDAC2 was also highly expressed in Hodgkin's lymphoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HDAC1, 2 and 3 are overexpressed in ovarian and endometrial carcinomas (Weichert et al, 2008a), prostate (Weichert et al, 2008b) and renal cancer (Fritzsche et al, 2008). HDAC1 is overexpressed in cancers of the breast , colon (Wilson et al, 2006) and pancreas (Wang et al, 2009b), whereas HDAC3 expression is increased in colon cancer (Wilson et al, 2006).…”
Section: Aberrant Expression Of Hdacs and Fusion Proteins In Cancermentioning
confidence: 99%